Parallel JPEG2000 Encoding on a Beowulf Cluster - Serra, A.; Dias, L.; Serrão, C.; Dias, J.; Trezentos, P. (Proc International Conference – Aplied Computig 2004, IADIS 2004, Lisboa, 2004)
This paper describes a methodology and computing architecture for the parallelization of an open-source JPEG2000 (or J2K) digital image encoder, applicable in Beowulf-type Clusters. It starts by providing an overview of the technical architecture solution chosen for the J2K image encoding cluster, justifying the choices made. The encoding algorithm is then presented, both in its original standalone as well as in the parallel versions, discussing which were the modifications performed in the original version to improve its performance on a high-performance computing platform, such as the Beowulf Cluster. Several tests were performed on the encoder, with the achieved results assessed by standard evaluation metrics of parallel algorithms. Those results are presented and discussed, showing the appropriateness of our approach. The major focus of this paper is on the High-Performance Computing aspects of the solution, reinforcing the idea that high-performance solutions may be obtained through relatively low-cost hardware architecture solutions. Finally, some conclusions are drawn, and the directions for future work are given.